Effects of habitat correlates on Himalayan red panda distribution in Mewa Watershed, Taplejung, Nepal - Sherpa, Manisha; Poudel, Tika Ram; Aryal, Prakash Chandra; Thapa, Arjun (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
The Himalayan red panda (Ailurus fulgens), belonging to Ailuridae family, is an endangered and habitat specialist carnivore with a peculiar feeding behaviour. A large proportion of potential habitat of the Himalayan red panda lies outside protected areas, which is inadequately assessed on the local scale. Mewa watershed in Taplejung District, eastern Nepal harbors a part of potential habitat of the Himalayan red panda, which has not been explored in terms of habitat requirement attributes of the species. Thus, the study attempted to determine habitat variables affecting distribution and habitat association of the Himalayan red panda in the Mewa watershed. Based on a grid-based survey design, the study deployed altitudinal transects (n = 45; 0.5 to 1 km length) to record animals’ evidence and ecological attributes and circular plots (n = 146) for vegetation assessment. Data were analyzed in ArcGIS 10.4.1 for mapping, and binary logistic regression analysis to determine the important habitat correlates. Signs of the Himalayan red panda were recorded in eight grids of the 14 survey grids between the range of 2,500 and 3,500 m elevation in the northeast and northwest aspects and between 15° and 40° slope. A total of 90.32% indirect and 9.67% direct evidence of the species were recorded in 31 plots. The Himalayan red panda defecates mostly in tree branches (56.36%) as the main substrate. Distance to water sources, bamboo clump presence and livestock activity were the important habitat components of the Himalayan red panda, which showed positive association with their distribution and marginal significance, whereas human trails and shrub richness were associated negatively. The study identified livestock activity and human trails as major threats to the Himalayan red panda and its habitat in the Mewa watershed. This study provides valuable insights into the important habitat attributes and potential threats faced by the species in the study area.